Chemical Pollution and Population Density in the Environmental Hadith Perspective - Syaputra, Mei Dian; Alfassa, Achmad Isya; Ihsanuddin, Ihsanuddin (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Rapid population growth intensifies industrial activities, urbanization, and the use of chemical substances, resulting in significant environmental pollution. In Islamic teachings, the principles of cleanliness and responsibility toward nature are strongly emphasized in various hadiths of Prophet Muhammad (peace be upon him), including the saying “At-thahuru syatrul iman” (cleanliness is part of faith) and the prohibition against causing harm or corruption on the earth. This article integrates perspectives from environmental chemistry, demography, and thematic hadith interpretation to examine the connection between population density, chemical pollution, and Islamic ecological values. Using an interdisciplinary literature review and qualitative descriptive analysis, the study finds that increasing population density without proper chemical management leads to environmental degradation that contradicts the Islamic principles of maslahah (public welfare) and khilafah fil ardh (human stewardship of the earth). The study concludes that Islamic ethical values can provide a strong moral foundation for developing environmentally sustainable and ecologically just policies.